User Satisfaction Analysis of M-Tix Application in Batam City Using the DeLone and McLean Model - Felix King Lie; Suwarno Suwarno (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2024)
M-Tix is an application that provides online movie ticket services, launched in 2015 and has been widely used. This study’ objectives are to determine the satisfaction level of M-Tix users in Batam City. This research used DeLone and McLean model, collecting data with quantitative method with 418 respondents and qualitative method with 30 informants as well as using SPSS and AMOS for data testing. This study’s findings indicate that all hypotheses have a positive impact between the variables and can be concluded that M-Tix users in Batam City are satisfied during the application usage.